Portacaval Shunt and Hyperlipidemia - Starzl, Thomas E. (1978)
The use of a completely diverting portacaval shunt for the purpose of lowering the serum concentration of cholesterol and low-density lipoproteins is reviewed and a recommendation provided that such a shunt for hyperlipidemia should be considered for type II individuals.